Early Osteoarthritis and Double-Layered Patella in a Patient With Multiple Epiphyseal Dysplasia - Selçuk SAYILIR; Timur EKİZ (Archives of Rheumatology, 2017)
Multiple epiphyseal dysplasia is a relatively rare skeletal dysplasia characterized with early osteoarthritis resulting in joint dysfunction and short stature in childhood. In this article, we presented a 42-year-old patient of multiple epiphyseal dysplasia who was newly diagnosed, had relatively normal height, osteoarthritis, and double-layered patella. The patient was diagnosed in adulthood in contrast to the literature because the clinical scenario was apparent in the late periods.